Analysis and Stochastics of Growth Processes and Interface Models [electronic resources] / Edited by Peter Mörters, Roger Moser, Mathew Penrose, Hartmut Schwetlick, Johannes Zimmer. - Mörters, Peter.
Includes biographical references and index.